Notary public’s obligation regarding bank secrecy post law number 4 of 2023 concerning financial sector development and strengthening - Usanti, Trisadini (Trigin Publisher, 2023)
A legal vacuum is found regarding the notary public as the affiliated party who is obliged to keep the bank secrecy in Banking Law and Law on Financial Sector Development and Strengthening. Although it cannot be denied that notary public have an important role in banking activities, e.g. in making authentic deeds related to granting credit or providing guarantees. The notary public also might obtain information related to the deposit customer and their savings if their savings are used as the object of credit collateral. The problem analyzed in this study is that in the absence of notaries public arrangements as an affiliated party, are they still obliged to keep the bank secrecy and what are the sanctions for notaries public if they violate the bank secrecy? The approach used in this study is the statute approach and the conceptual approach. This study found that to fill the legal vacuum, a legal discovery could be performed using grammatical interpretation, extensive interpretation, and legal construction with analogical reasoning regarding Article 40, Article 1 number 21, and Article 40 C in Law on Financial Sector Development and Strengthening, therefore based on these methods, notary public is part of the affiliated party which obliged to keep the bank secrecy. As for the bank secrecy violation, the sanction is not limited to imprisonment and fines, but also additional punishment as regulated in the Law on Financial Sector Development and Strengthening. In addition, there is a possibility of a tort lawsuit for the losses caused and administrative sanctions for notaries public based on Article 16 paragraph (11) of Law on Notary Public Position.